Unusual Case of an Infant with Urinary Tract Infection Presenting as Cholestatic Jaundice - Rahaf Niazi; Bashaer Baharoon; Afnan Neyas; Meshari Alaifan; Osama Safdar (Case Reports in Nephrology)
Neonatal jaundice is considered one of the most common reasons for admission to the pediatric medical ward. We report a case of a 1-month-old infant who presented with jaundice but no fever or any other signs of systemic illnesses. Laboratory test results revealed high direct hyperbilirubinemia, and urine culture showed a urinary tract infection with Enterobacter cloacae as the causative agent. He was admitted to the pediatric medical ward where he was treated with a course of antibiotics for 14 days, and cholestasis resolved completely following a course of antibiotics. We conclude that direct hyperbilirubinemia can be related to urinary tract infection in neonates. It is unusual for urinary tract infection to present clinically and biochemically as cholestatic jaundice.